The Influence of Fiscal Policy Credibility on Inflation Stability in Indonesia - Gulo, Ahmad Jumadin; Syafii, M. (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2025)
Study This aiming for know How impact tax, expenditure government, tribe interest, investment, value exchange, export and debt abroad against inflation in Indonesia and knowing factor tax, expenditure government, tribe interest, investment, value exchange, export and debt abroad in together to inflation in Indonesia. The things studied How impact tax, expenditure government, tribe interest, investment, value exchange, export and debt abroad against inflation in Indonesia. With using secondary data with range 10 years time and data management using method Confirmatory Factor Analysis (CFA) and Multiple Linear Regression. Research This in the background behind consideration that high and uncontrolled inflation stable give impact negative to condition economic and social. Impact negative the make inflation as one of the disease the economy that exists in every country, both in developed countries as well as in developing countries. Indonesia itself in 2013 the rate inflation return increase reach the figure of 6.41 percent, which was caused by the existence of increase price bbm (material) burn oil) which continues trigger increase price transport general as well as increase material food. Based on results testing Confirmatory Factor Analysis (CFA) in the table KMO and Bartlett's test show mark exchange and investment significant to inflation in Indonesia, while tax, expenditure government, tribe interest, exports and debt overseas has a negative influence or No significant to inflation in Indonesia and based on f-test results (hypothesis test) simultaneous shows that mark exchange and investment in a way simultaneously influential positive and significant to inflation in Indonesia.